Overexpression of the phospholipase A2 group V gene in glioma tumors is associated with poor patient prognosis - Wu, Changwu (Cancer Manag Res, 2019)
Purpose: Gliomas are the most common primary malignant neoplasms of the central nervous system. Secreted phospholipases A2 (sPLA2s) are known to play an important role in various physiological processes, including bioactive lipid production, defense mechanisms, and cell signaling. However, their roles and clinical importance in gliomas remain unclear. Patients and methods: In this study, we analyzed the association between the expression of various sPLA2-encoding genes and the clinicopathology of gliomas, using the data of 1047 patients obtained from a public database. Immunohistochemical analysis of 82 glioma tissues was also carried out to assess the relationship between phospholipase A2 group V (PLA2G5) protein expression and the World Health Organization (WHO) glioma grades. Results: We found that high PLA2G5 gene expression was associated with unfavorable prognosis in both low-grade and high-grade gliomas. The immunohistochemistry of the 82 glioma tissues further confirmed that PLA2G5 protein expression was dependent on the WHO glioma grade. In addition, we found a correlation between PLA2G5 gene expression and both epithelial–mesenchymal transition and the isocitrate dehydrogenase 1 mutation status in these tumors. Conclusion: Our results indicate that PLA2G5 could be a potential biomarker for predicting poor prognosis in patients with gliomas.